High fluency can improve recognition sensitivity based on learned metacognitive expectations - Esser, Sarah; Lustig, Clarissa; Haider, Hilde (Frontiers in Psychology, 2022)
Fluency of processing has shown to influence recognition judgements. Fluency most commonly induces a liberal response bias to judge fluently processed information as well-known because knowledge of a high correlation between the frequency of encounters, memory strength and thus fluency of processing has been acquired in the past. In this study we aimed to show that high fluency can increase recognition judgement sensitivity as well if the participants had encountered fluent and non-fluent processing during training. Thirty-three participants have been trained with a 12-element sequence in a Serial Reaction Time Task. During training, the response stimulus interval alternated block-wise between constant (fluent) and variable (non-fluent). Participants showed a higher capability of discriminating between old and new test sequences under fluent than under non-fluent test conditions. Furthermore, participants did not show any liberal or conservative bias after they have been trained with alternating fluency.